Quantifying the impact of structural reforms - Ekkehard Ernst; Gang Gong; Willi Semmler; Lina Bukeviciute (European Central Bank (ECB), 2006)
We estimate a dynamic, intertemporal optimisation model that mimics features of European labour markets, such as sticky nominal wages and sluggish adjustment of employment to shocks for 15 OECD countries. The estimates include a measure for the degree of labour market sluggishness that compares well with standard indicators of product and labour market regulation. Calibration of the model on a selected country sample confirms its explanatory power in comparison with the standard competitive markets model. In a second step, the measure for labour market sluggishness is used as a policy variable and model variants are simulated in order to assess the extent to which the countries would have performed better with more flexible labour markets. These policy experiments show that an increase in labour market flexibility reduces the volatility of consumption relative to production, improves intertemporal efficiency but entails higher employment risk.
Keywords: E32; C61; 330; business cycles; labour market reforms in OECD countries; nominal and real rigidities; non-clearing labour markets; Strukturwandel; Messung; Arbeitsmarkt; OECD-Staaten